(untitled) (Rev. Anal. Numér. Théor. Approx., 1999)
Book reviews for: JAMES W. DEMMEL, Applied Numerical Linear Algebra, SIAM, Philadelphia, 1997, ISBN 0-89871-389-7, xi+419 pp. Reviewed by E. Catinas. GREENBAUM, Iterative Methods for Solving Linear Systems, SIAM, Philadelphia, 1997, ISBN 0-89871-396-X, xiii+220 pp. Reviewed by E. Catinas. MATZEU, A. VIGNOLI, Topological Nonlinear Analysis II Degree, Singularity and Variations, Birkhauser, Boston-Basel-Berlin, 1997, 601 pp., ISBN 0-8176-3886-5. Reviewed by R. Precup. GHEORGHE MICULA and SANDA MICULA, Handbook of Spline, Kluwer Academic Publisher, Dordrecht/Boston/London. Reviewed by I. Pavaloiu. M.G. NADKARNI, Basic Ergodic Theory, Birkhauser Advanced Texts, Birkhauser Verlag, Basel-Boston-Berlin, 1998, vi+149 pp., ISBN 0-8176-5816-5 and 3-7643-5816-5. Reviewed by S. Cobzas. M.G.NADKARNI, Spectral Theory of Dynamical Systems, Birkhauser Advanced texts, Birkhauser Verlag, Basel-Boston-Berlin, 1998, vii+182 pp., ISBN 0-8176-5817-3 and 3-7643-5817-3. Reviewed by S.Cobzas. SERGEY BAGDASAROV, Chebyshev Splines and Kolgomorov Inequalities, Operator Theory-Advances and Applications, vol.105, Birkhauser Verlag, Basel-Boston-Berlin, 1998, ISBN 3-7643-5984-6 and 0-8176-5984-6, xiii+205 pp. Reviewed by C. Mustata. G.H. GOLUB and C.F. VAN LOAN, Matrix Computations, third edition, The Johns Hopkins University Press, Baltimore and London, 1996, ISBN 0-8018-5413-X, xxvii+694 pp. Reviewed by E. Catinas. Statistical and Probabilistic Models in Reliability, D.C. Ionescu and N. Limnios (Editors) Statistics for Industry and Technology, Birkhauser Verlag, Basel-Boston-Berlin, 1999, xxxvi+352 pp., ISBN 0-8176-4068-1. Reviewed by C. Mustata. PREM K. KYTHE, Computational Conformal Mapping, Birkhauser Verlag, Basel-Boston-Berlin, 1998,xvi+462 pp.,ISBN 3-7643-3996-9 and 0-8176-3996-9. Reviewed by S. Cobzas. WERNER C.RHEINBOLDT, Methods for Solving Systems of Nonlinear Equations, SIAM, Philadelphia, 1998, CBMS-NSF Regional Conference Series in Applied Mathematics, ISBN 0-89871-415-X,ix+148 pp. Reviewed by E. Catinas. Mathematical Essays in honour of Gian-Carlo Rota, Bruce E. Sagan and Richard P. Stanley (Editors), Progress in Mathematics, vol.161, Birkhauser Verlag, Basel-Boston-Berlin, 1998, 463 pp., ISBN 0-8176-3872-5 and 3-7643-3872-5. Reviewed by I. A. Rus.